2016
DOI: 10.1111/dom.12713
|View full text |Cite
|
Sign up to set email alerts
|

Dogfish glucagon analogues counter hyperglycaemia and enhance both insulin secretion and action in diet‐induced obese diabetic mice

Abstract: Overall, dogfish glucagon co-agonist analogues had several beneficial metabolic effects, showing therapeutic potential for type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…Subsequent clinical studies of oxyntomodulin demonstrated significant efficacy concerning weight loss, resulting from the combined reduction of energy intake and increase of energy expenditure . As natural gastrointestinal hormones such as GLP‐1, glucagon or oxyntomodulin are rapidly degraded by serum proteases and are renally cleared, a number of stabilized oxyntomodulin analogs, as well as GLP‐1R/GCGR dual agonists based on glucagon, have been described as therapeutic agents for the management of obesity and associated metabolic disorders such as type 2 diabetes. However, the apparent challenge associated with translating the beneficial weight loss associated with a dual GLP‐1R/GCGR agonist is to curb the potential glucose‐elevating effects associated with excess glucagon pharmacology.…”
Section: Discussionsupporting
confidence: 91%
“…Subsequent clinical studies of oxyntomodulin demonstrated significant efficacy concerning weight loss, resulting from the combined reduction of energy intake and increase of energy expenditure . As natural gastrointestinal hormones such as GLP‐1, glucagon or oxyntomodulin are rapidly degraded by serum proteases and are renally cleared, a number of stabilized oxyntomodulin analogs, as well as GLP‐1R/GCGR dual agonists based on glucagon, have been described as therapeutic agents for the management of obesity and associated metabolic disorders such as type 2 diabetes. However, the apparent challenge associated with translating the beneficial weight loss associated with a dual GLP‐1R/GCGR agonist is to curb the potential glucose‐elevating effects associated with excess glucagon pharmacology.…”
Section: Discussionsupporting
confidence: 91%
“…We have previously successfully exploited highly conserved amino acid sequences from phylogenetically ancient fish in the search for naturally occurring, enzymatically stabilized, peptide hormone receptor agonists; including glucagon and GLP‐1 . The primary structures of bowfin, sea lamprey, sturgeon and trout PYY (1–36) peptides are shown in Table , and compared to human PYY (1–36) and NPY, since these are established NPYR1 agonists .…”
Section: Discussionmentioning
confidence: 99%
“…Further important structure/function knowledge relating to the NPY family of peptides concerns the characteristic “PP‐fold” conformation, responsible for bringing the N‐ and C‐terminal ends of the peptide in close contact to be recognized by the NPYR1 . This PP‐fold is characterized by the poly‐proline N‐terminal segment, Pro‐Pro‐Pro, stabilized by a Pro residue situated either at position 13 or 14 and folded back on a long amphipathic α‐helix, interacting with Tyr and Tyr Notably, these residues are all conserved across the four piscine PYY (1–36) sequences. Taken together, the fundamental structural characteristics necessary for specific human NPYR1 binding and activation are present within bowfin, sea lamprey, sturgeon and trout PYY (1–36) peptide sequences.…”
Section: Discussionmentioning
confidence: 99%
“…injections (9 am and 5 pm ) of either 0.9% saline vehicle (lean and high‐fat‐fed control group) or apelin‐13 amide, (pGlu)apelin‐13 amide or exendin‐4(1‐39), each at 25 nmol/kg body weight, over a 28‐day treatment period. This dose was chosen on the basis of previous experience with peptides …”
Section: Methodsmentioning
confidence: 99%
“…and oral) and metabolic response to feeding, were examined in overnight (12 hours) fasted lean and DIO mice treated with either peptides or saline as described previously . Whole‐body insulin sensitivity tests (25 U/kg body weight) were carried out as described previously using fed mice …”
Section: Methodsmentioning
confidence: 99%